Sidelobe Suppression in Array-Pattern Synthesis Using Periodic Leaky-Wave Antenna and Binomial Array. (11th November 2020) - Aziz, Hicham; Moubadir, Mahmoud; Farkhsi, Abdelkrim; Amar Touhami, Naima
Abstract : This paper presents the conception and realization of a 2D antenna array using periodic leaky-wave antenna (PLWA) and the binomial array (BA) at 6 GHz as the application of WLAN. The series array of periodic leaky-wave antenna was provided by an array of five rectangular Patches connected by cross lines. The nonuniform amplitudes of the binomial array are used to reduce the sidelobe level; in this way, the center source radiates strongly on the broadside. The prototype of the proposed 2D antenna array is designed, fabricated, and tested. A good agreement is obtained between simulated and measurement results.